Systematics and cladistics of a new Naupactini genus (Coleoptera: Curculionidae: Entiminae) from the Andes of Colombia and Ecuador - Río, María Guadalupe del (2012)
A new genus of broad-nosed weevils belonging to the tribe Naupactini (Coleoptera: Curculionidae) is described, based on six species from the Páramo-Puna subregion (Andean region) of South America. Three species are new and three have been transferred from the genus Asymmathetes (Asymmathetes nigrans, Asymmathetes rugicollis, and Asymmathetes vulcanorum). The new genus is recognized by the black, denuded, and shiny tegument, the well-developed pre-epistome, the elytral base curved backwards on middle, the reduction of the hindwings, and the widely separated procoxae, closer to the anterior than to the posterior margin of the prosternum. A cladistic analysis of the six species of the new genus plus five out-groups (Amitrus, Amphideritus, Asymmathetes, Melanocyphus, and Trichocyphus), using 49 morphological characters, resulted in a single cladogram. © 2012 The Linnean Society of London.